Masuknya Islam dan Munculnya Bima sebagai Pusat Kekuasaan Islam di Kawasan Nusa Tenggara - Tawalinuddin Haris (Jurnal Lektur Keagamaan, 2012)
When Islam came to Bima is not definite yet, but from many information in traditional historiography that Islamization goes on with penetration of pacifique, by trading, preaching and marriage and by power or civil war. Bima emerged as a central of Islamic power about seventeenth century, when the fifth king of Bima converted to Islam and than used title Sultan Abdul Kahir. As a center of Islamic power, Bima grew and reached its glorious on the rule of Sultan Abdul Khair Sirajudin and Sultan Nurudin. In this period, many Moslem scholars came to Bima from many territories of archipelago for disseminating and teaching Islam to Bima society.